Reproduction, growth and longevity of the endemic South American crab Aegla marginata (Decapoda: Anomura: Aeglidae) - Da Silva, Alexandre Ribeiro [UNESP]; Wolf, Milena Regina [UNESP]; Castilho, Antonio Leão [UNESP] (Taylor & Francis, 2016)
Reproduction, growth and longevity of Aegla marginata sampled with traps in Intervales State Park (Brazil) from October 2013 to December 2014 are described. Male and female carapace lengths (CL) ranged in size from 5.50 to 20.00 mm and 5.20 to 19.67 mm, respectively. Functional sexual maturity was determined at a CL of 9.28 mm. The main reproductive period occurred during colder seasons (autumn and winter, March-August). Egg number varied between 40 and 146 (mean ± SD; 95 ± 31.5), with an average reproductive output of 10.8% of the female weight, a value close to that found in other anomurans, enough to guarantee the success of this species during embryonic development. Fecundity increased with animal size (ANCOVA, p < 0.05), which allows an animal to produce more eggs, maximising reproductive efficiency, according to its size. Sex ratio was skewed towards males (Chi-Square, p < 0.05), especially during the reproductive period, in which females tended to exhibit cryptic behaviour when incubating eggs. The number of females and males was similar in the months before reproduction, suggesting that females were more active looking for food to store energy for the next reproductive period, and/or were looking for mates. The longevities of 2.43 (males) and 2.49 (females) years (Von Bertalanffy method) corroborate other studies that estimated a longevity of 2 to 3.3 years for Aegla spp. We conclude that A. marginata has seasonal reproduction and recruitment. All the information gathered here should be useful to future studies with other populations of A. marginata outside protected areas.
Keywords: Fecundity; latitudinal variation; life span; reproductive periodicity; sex ratio